Analyzing Analyzing the Role of Cross Border Trade Policies in Facilitating Pak- Afghan Trade Post –Taliban - Haidari, Mohammad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
With the war in Afghanistan spanning over 13 years coming to an inconclusive end, the three multiple transition processes (security, political and economic) have begun. Afghan security forces are assuming greater responsibility and leadership in the country along with the formation of a new political setup. Despite gains from the last decade, Afghanistan continues to be challenged by a plethora of problems, and is far from being stable. Afghanistan will continue to present challenges to the international community, its region and its neighboring states, particularly Pakistan. Given its proximity to Afghanistan and its involvement in the war against terrorism (now referred to as the ‘overseas contingency operations’), Pakistan is perhaps the most important regional player that has always been directly affected by events in that country. Although the challenges Afghanistan faces are domestic in nature, they have a direct impact on Pakistan as they, among others, stem from the porous nature of the Pak-Afghan border. Therefore, in such a scenario, a macro-level assessment of security risks that Pakistan may face in the aftermath of the withdrawal is essential. The main objective of the current investigation are to analyze the role of cross border policies in facilitating Pak-Afghan Trade Post- Taliban. Qualitative research methodology adapted to intricate dynamics of Pak-Afghan relations, particularly in the context of security and defense. These methodology included content analysis on refugees, security agreements, trade policies, defense strategies and shed light on the multifaceted aspects of this complex relationship. During study detail explores the historic relations among both countries and how ties up such security issues of post 9/11. Pakistan decided to support the U.S. policy of war on terrorism and this meant Pakistan officially went to war against the Taliban. Pakistan's goal is to see a stable Afghanistan, but if the U.S. would withdraw its forces, elements in Pakistan might once again be tempted to favor the Pashtuns in the governance of Afghanistan.